2013
DOI: 10.1016/j.cub.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of Crumbs Function and Regulation in Tissue Morphogenesis

Abstract: Establishing and maintaining epithelial polarity is crucial during development and for adult tissue homeostasis. A complex network of evolutionarily conserved proteins regulates this compartmentalization. One such protein is Crumbs, a type I transmembrane protein initially shown to be an important apical determinant in Drosophila. We discuss recent studies that have advanced our understanding of the function and regulation of Crumbs. New findings obtained in flies and fish, reporting homotypic interactions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 47 publications
2
59
0
Order By: Relevance
“…Crb regulates apicobasal polarity in Drosophila (Tepass, 1996) as well as in vertebrates (Bazellieres et al, 2009;Roh et al, 2003). More recently, Crb has been recognized as having a distinct role regulating the positioning and stability of adherens junctions (AJs) during such processes as the formation of the salivary gland and rhabdomere biogenesis during pupal eye development (Campbell et al, 2009;Klose et al, 2013;Letizia et al, 2011;Morais-de-Sá et al, 2010;Muschalik and Knust, 2011;Röper, 2012;Pocha and Knust, 2013;Tepass, 2012;Walther and Pichaud, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Crb regulates apicobasal polarity in Drosophila (Tepass, 1996) as well as in vertebrates (Bazellieres et al, 2009;Roh et al, 2003). More recently, Crb has been recognized as having a distinct role regulating the positioning and stability of adherens junctions (AJs) during such processes as the formation of the salivary gland and rhabdomere biogenesis during pupal eye development (Campbell et al, 2009;Klose et al, 2013;Letizia et al, 2011;Morais-de-Sá et al, 2010;Muschalik and Knust, 2011;Röper, 2012;Pocha and Knust, 2013;Tepass, 2012;Walther and Pichaud, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…132 In vertebrates, three different Crumbs isoforms (CRB1, CRB2, and CRB3) with largely nonoverlapping expression patterns are found, CRB3 being the major isoform in epithelial cells. 133 Via their C-terminus, Crumbs proteins bind PALS1 (protein associated with Lin-7 1), an adapter protein that forms a complex with the multi-PDZ domain protein PATJ (PALS1-associated tight junction protein) (Figure 3(a)).…”
Section: Crumbs Complexmentioning
confidence: 99%
“…Over the last two decades, genetic and cell biology studies have identified three tripartite protein complexes, namely the crumbs (Crb) 3 complex composed of Crb⅐PALS1⅐PALS1-associated tight junction (PATJ), the partition-defective (PAR) complex composed of PAR3/PAR6/ aPKC, and the Disc large (DLG) complex composed of DLG/ lethal giant larvae (LGL)/Scribble, as the principle cell polarity regulators (5)(6)(7)(8)(9)(10). Among these regulators, only Crb is a transmembrane protein and necessary for both the apical-basal cell polarity and the assembly of the zonula adherens in Drosophila epithelia (11)(12)(13). In early Drosophila embryo development, dysfunction mutations of Crb lead to the loss of the apicalmembrane identity, and overexpression of Crb causes expansion of the apical-membrane size at the expense of the basolateral membranes (14,15).…”
mentioning
confidence: 99%